Borders of physical self in virtual reality: a systematic review of virtual hand position discrepancy detection - Antoš, David; Švec, Tomáš; Hořínková, Jana; Bartečková, Eliška (Frontiers in Psychiatry, 2025)
IntroductionVirtual reality (VR) holds significant promise for psychiatric research, treatment, and assessment. Its unique ability to elicit immersion and presence is important for effective interventions. Immersion and presence are influenced by matching—the alignment between provided sensory information and user feedback, and self-presentation—the depiction of a user’s virtual body or limbs. Discrepancies between real and virtual hands can affect the sense of presence and thus treatment efficacy. However, the precise impact of positional offsets in healthy individuals remains under-explored. This review assesses how various factors influence the detection thresholds for positional offsets in VR among healthy subjects.MethodsA comprehensive database search targeted English-language studies on the detection thresholds of virtual hand positional offsets using head-mounted displays (HMDs) with specific tracking capabilities. Data on methodologies, participant demographics, and VR system specifics were extracted.ResultsThirteen studies met the inclusion criteria, revealing significant variability in detection thresholds—from a few millimeters to 42 cm for linear shifts and from 2° to 45° for angular shifts. Sensitivity to these offsets was affected by hand movement direction and magnitude, hand representation realism, and the presence of distractions. VR system specifications, such as resolution and tracking accuracy, also played a significant role. Methodological issues included small sample sizes, inadequate demographic reporting, and inconsistent presence or avatar embodiment measures.ConclusionThe results highlight the need to consider identified influencing factors to maximize user presence in VR-based therapies. Variability in VR device capabilities also emphasizes the need for detailed reporting of device properties in research. The individual variability in offset detection further illustrates VR’s potential as a tool for studying body ownership and multisensory integration.